COVID-19 and ocular implications: an update - Raffaele Nuzzi (Journal of Ophthalmic Inflammation and Infection, 2020)
Abstract Background COronaVIrus Disease 19 (COVID-19) was first reported in Wuhan, China in December 2019 and is now pandemic all over the world. The purpose of this review is to highlight the possible ocular presentation of COVID-19 infection and the consequence of the pandemic in the daily ophthalmology routine. A total of 9 articles was included by searching PubMed database for articles published between December 2019 and April 2020. Main body Conjunctivitis (and keratoconjunctivitis) can be the first symptom in infected patients. The virus can be present in tear and conjunctival secretions, requiring maximum attention. It’s important to understand if COVID-19 could spread through the ocular route or present as the primary infected site. Ocular implications should also be considered for therapy. In fact, one potential treatment is chloroquine and its derivatives, including hydroxychloroquine. Hydroxychloroquine, in fact, can induced retinal toxicity. The exponential increase in lthe number of Covid-19 cases was like a tsunami for health care companies, which were not ready to face this emergency. Ophthalmology departments were also affected by the reorganization of healthcare services. Conclusion The studies analaysed have some limitations. First, the sample size and the covered population consisted mainly of patients with mild disease. Moreover, the studies are often descriptive study, without a correlation analysis. Finally, no normal population was observed in the studies, so a normal control group should be included for comparison in future studies. With the evolving COVID-19 pandemic and with its high infectivity, it is necessary to rearrange ophthalmologist routine clinical practice in order to control viral spread and try to maximize patient and health-care provider’s safety.